Duobinary modulation/predistortion techniques effects on high bit rate radio over fiber systems - Mahmoud M. A. Eid; Ashraf S. Seliem; Ahmed Nabih Zaki Rashed; Abd El-Naser A. Mohammed; Mohamed Yassin Ali; Shaimaa S. Abaza (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The work has presented duobinary modulation and predistortion techniques for the radio over fiber system enhancement for achieving security level. Duobinary modulation technique has more compact modulated spectral linewidth with standard non return to zero modulation code. Different NRZ/RZ rectangle shape employed that are namely exponential rectangle shape (ERS), and Gaussian rectangle shape (GRS) for different transmission bit rates. Switching bias voltage, and switching RF voltage based LiNbO3 modulator are changed to measure the performance parameters of the radio over fiber (RoF) system. Predistortion technique improves the linearity of transmitter amplifiers and it is considered as a power efficiency technique. The optimum values of the Q-factor, data error rate (BER), electrical power, signal gain, noise figure, and light signal/noise ratio are achieved with 8 Volt for both switching biases/switching RF signal at 100 GHz. Signal quality/BER and electrical power after the receiver enhancement ratio by using this technique at different RF signal frequencies.